Investigation of relationship between multiple intelligences of higher degree students (2020)
Research into investigation of the relationship between multiple intelligence of learners and academic performance is germane. This study investigated relationship between multiple intelligences of higher degree students and academic performance. Two research questions and three hypotheses guided the correlational study. Three hundred and thirty Master degree students of the University of Ibadan who are randomly selected made the sample. Three validated instruments: Simple Multiple Intelligence Inventory developed by Gardner (r=0.89), Modified MILHDSQ (r=0.87) and the CGPA of students result for the two semesters was used to collect data that was analysed using descriptive and inferential statistics at 0.05 level of significance. The result reveals a very high level of multiple intelligences in the overall mean of 4.34. Students demonstrated very much high intelligence in Logical-mathematical (Xw=4.82), interpersonal (Xw=4.57) and visual (Xw=4.53). Both logical (8.143<0.05) and intrapersonal (19.252<0.05) intelligences are related to academic performance. Moreover, academic performance has high correlation with Logical (0.72) and Linguistic (0.61). This shows a positive correlation between multiple intelligences and academic performance. The result provided opportunity for lecturers’ awareness to observe level of multiple intelligences of students for better guidance to improve academic performance. It is recommended that teaching strategies that will accommodate multiple intelligences be designed by education stakeholders.